Safety assessment of rosuvastatin-fenofibrate combination in the treatment of hyperlipidemia based on FDA’s adverse event reporting system database - Li, Qun; Shan, Wenya; Wu, Saiwei (Frontiers in Pharmacology, 2025)
BackgroundWith the improvement of living standards, an increasing number of patients are presenting with mixed hyperlipidemia. In addition to cholesterol reduction, it is imperative to lower triglyceride levels. The combination of statin and fibrate for reducing lipid levels has commonly been applied in clinical therapy. However, the combination of drugs also increases the risk of adverse events (AEs). In this study, we analyzed the safety signals of rosuvastatin-fenofibrate combination by assessing the publicly available US Food and Drug Administration Adverse Event Reporting System (FAERS), so as to provide a reference for rational clinical use of rosuvastatin and fenofibrate, and reduce the occurrence of related AEs.MethodsReports to the FAERS from 1 January 2004 to 19 March 2020 were analyzed. The proportional report ratio (PRR), reporting odds ratio (ROR), and Bayesian Confidence Propagation Neural Network (BCPNN) analysis were used to extract data from FAERS for suspected signals referring to the combination of rosuvastatin and fenofibrate.ResultsA total of 68 safety signals were detected from the top 250 AEs in 3,587 reports, of which 28 signals were not included in the drug labels. All the detected AEs were associated with 12 System Organ Classes (SOC), such as gastrointestinal, musculoskeletal and connective tissue, general diseases, investigations and nervous system. The most frequent AEs were analyzed, and it was found that women generally have a higher susceptibility to experiencing AEs, including pain, nausea, fatigue, myalgia, diarrhea, dyspnea, headache, weakness, and dizziness.ConclusionClinicians should pay more attention to the AEs of gastrointestinal and muscular system during combination therapy, and it is recommended to strengthen pharmaceutical care during clinical application.